The Effect of Information Technology Utilization and Service Quality on User Satisfaction with Local Government Financial Information Systems - Nasution, Siti Nur Fadhilah; Syahrani, Annisa; Astari, Prilia; Irawan, Irawan (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study aims to formulate a conceptual model that explains the influence of information technology utilisation and service quality on user satisfaction with the Regional Financial Information System (SIKD). The main problems identified include low optimisation of SIKD feature usage, inconsistent technical support, limited training, and a gap between the expected benefits of the system and the actual user experience. To address these issues, this study uses a conceptual exploratory design through a conceptual modelling and content analysis approach, reinforced by a literature review, regulatory analysis, and a synthesis of the latest research findings related to public sector information systems. The analysis techniques used include mapping the elements of information technology utilisation, evaluating service quality based on a digital service quality model, and gap analysis to identify the determinants of user satisfaction in the context of regional finance. Through this approach, the study is expected to produce a conceptual model that contains the logical relationship between the components of technology, services, and user satisfaction with SIKD, which can be the basis for developing strategies to increase system utilisation, strengthen technical service support, and improve digital governance of regional financial management. The model is expected to contribute to the continuous improvement of the quality of SIKD implementation and support the creation of more effective, transparent, and accountable regional financial governance.